(untitled) (ENTHYMEMA, 2016)
This article attempts to define the form that action takes when it is the focus of narrative plot, in a manner that avoids certain detours in the interpretation of narrative phenomenon and its anthropological function. Two such detours are evoked at the outset. First, structuralist narratology has had a tendency to analyze the “actional” structures of the narrative fabula autonomously. This has led narratalogists to lose sight of the function that actions have in conversational, or oral narrative, and to generalize a theory of action from this partial view. Second, cognitive theorists, despite having decompartimentalized narrative structures, have generally based their work on a schematic model of intentional action that is too general and too simplistic to properly determine the function that narrated actions fulfill. The author highlights the ways that certain forms of narrated action produce suspense or curiosity when used in conversational narrative. Drawing attention to the fundamental role of polemical actions in the dynamics of narration allows oppose two complementary conceptions of action: whereas “narrative” approaches highlight the uniqueness, the under-determinedness, or the surprising character of the narrated event, other forms of analysis seek to draw attention to the rules behind the apparent novelty of the event.